Analysis of the evolution of watershed habitat quality and its drivers under the influence of the human footprint - Jiang, Yinghong; He, Jing; Zhai, Duanqiang; Hu, Chuyan; Yu, Long (Frontiers in Environmental Science, 2024)
Habitat quality (HQ) serves as a pivotal metric for assessing biodiversity and ecosystem health, with alterations in land use driven by human activities posing direct implications on HQ and ecological sustainability within river basins. Prior research on HQ has predominantly centered on historical land use changes, neglecting the comprehensive consideration of future land use transformations and ecological zoning strategies' influence on HQ. Consequently, this investigation simulates potential land use shifts in the Min River Basin across various future scenarios, leveraging the integration of PLUS and InVEST models, quantitatively dissects HQ's responsiveness to these changes and delves into the spatial differentiation dynamics underlying these responses, while also exploring the drivers behind such differentiation. Synergizing with the Human Footprint Index (HFI), the study devises a rational ecological zoning plan tailored to the region and outlines targeted control measures for each zone. The results of the study showed that: (1) the east-central part of the Min River Basin was subject to a greater degree of human interference, and the trend of interconversion between grassland, forest land, and cropland was relatively significant, with construction land mainly originating from the transfer of cropland; (2) from 2000 to 2020, average HQ scores for priority protected zones, priority recovery zones, and appropriate development zones stood at 0.9372, 0.2697, and 0.6098, respectively, accompanied by a rise in the proportion of low and moderate HQ areas to 15% and 17%; (3) DEM and Slope were the main drivers affecting HQ, and their explanatory power reached 0.519 and 0.426, respectively; (4) in comparison to a natural development scenario (ND), the planning protection scenario (PP) offers greater promise for ecological preservation and sustainable development within the Min River Basin. The research results can provide technical support for the ecological restoration of land resources and the development and protection of national land space in watershed areas.